2016
DOI: 10.1371/journal.pone.0159967
|View full text |Cite
|
Sign up to set email alerts
|

Ethosomes Loaded with Cryptotanshinone for Acne Treatment through Topical Gel Formulation

Abstract: The aim of this study was to develop ethosomes loaded with cryptotanshinone (CPT) and formulate them as a topical gel for the treatment of acne. Ethosomes were prepared and evaluated for vesicle size, CPT loading and encapsulation efficiency. Optimized ethosomes were formulated as Carbomer 974 gels and compared with conventional hydroethanolic gels for transdermal permeation and skin deposition in vitro. The anti-acne activity and skin irritation of the gel was investigated in rabbits. Optimized ethosomes had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…110 More examples of herbal loaded NE are presented in Table 1. 88,111,112 Dendrimer A dendrimer is a tree-like synthesized polymer that was characterized as having a single central core that gives frequent branches of variously armed macromolecules (external capping and multifunctional groups) ( Figure 6) to achieve better targeting to specific sites. Generally, they are made up of natural or synthetic components such as sugars, nucleotides and amino acids.…”
Section: Transferosomementioning
confidence: 99%
“…110 More examples of herbal loaded NE are presented in Table 1. 88,111,112 Dendrimer A dendrimer is a tree-like synthesized polymer that was characterized as having a single central core that gives frequent branches of variously armed macromolecules (external capping and multifunctional groups) ( Figure 6) to achieve better targeting to specific sites. Generally, they are made up of natural or synthetic components such as sugars, nucleotides and amino acids.…”
Section: Transferosomementioning
confidence: 99%
“…19 However, the mechanisms by which ethosomes promote skin penetration of drugs remain elusive. 20,21 Therefore, the following three key questions are critical: Which key ingredient(s) in ethosomes is responsible for their excellent properties in promoting percutaneous penetration? Can ethosomes penetrate into the skin with an intact vesicle structure?…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31] In terms of possible mechanisms for ethosomes to promote percutaneous permeation of drugs, two viewpoints have been presented: the first one is that ethanol is a known penetration enhancer, which can disturb the multilamellar and ordered lipid domain, lower the structure density, and enhance the fluidity of the stratum corneum, thus providing the vesicles with flexible characteristics that allow them to penetrate easily into deeper layers of the skin; 32,33 the second one is that phospholipids between the stratum corneum and ethosomal vesicle fuse easily, thus changing the transition temperature, leading to enhanced drug penetration. 34 In our research, we interestingly found that even though the lipid content in the liposomes and the ethanol content in the hydroethanolic solution were equal with those in the ethosomes, after percutaneous penetration, a greater fluorescence intensity in the skin of the ethosomal system was observed, compared with that in the hydroethanolic solution and liposomes (P,0.05; Figure 2B).…”
mentioning
confidence: 99%
“…The skin deposition and permeation studies on pig skin show that ethosomal gel was significantly superior to conventional hydroethanolic gel. Reports suggested that ethosomal gel are efficient vesicles for cryptotanshinone dermal delivery for acne treatment, which efficiently permeates the drug across rat skin and target pilosebaceous unit for baldness [12][13][14]. Mechanistically, ethosomes have a synergistic effect of their ingredients with skin lipids and showed transdermal superiority over liposomes and hydroethanolic solution.…”
Section: Introductionmentioning
confidence: 99%